RETRACTED: Application of genetically engineered biopharmaceutical products in children with various JIA forms in the Karaganda region - Kenzhetaeva Tattigul; Serikova Gulmira; Alimshaikhina Kulzhazira; Issayeva Aiman; Sabiyeva Makpal; Sarmankulova Gulmira (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001